ANALISA KUAT LELAH ALUMUNIUM 6063-TF PADA MESIN UJI ROTARY BENDING - Rasma, Rasma (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2012)
ABSTRACT. Part of deformations occurs in the structure or construction of machine elements which are subject to dynamic loading during operation due to fatigue that happens without any preliminary signs, causing significant damages and losses. Fatigue strength is a process of local change within the structure, occuring permanently with the course of time due to a condition where stress or strain occurs, causing cracks or fractures after repeated loadings. Surface roughness factor which affects fatigue was applied in analysis and machining, that samples were smoothly and roughly machined. Analysis was performed on AL 6063-TF alloy which is often used for motorized vehicles. To understand the effect of surface roughness factor on fatigue, series of fatigue strength tests were carried out using Rotary Bending Fatigue Test method until cycle values or fatigue age and certain stress value were adequately obtained to prepare a S-N semi log plot using statistical calculations.